Detailed experimental and numerical investigation of fluid–particle interactions of a fixed train of spherical particles inside a square duct. (June 2018) - Ramezani, M.; Sun, B.; Subramaniam, S.; Olsen, M.G.
Highlights: Investigation of fluid flow around a train of five spherical particles. Comparison of detailed experimental measurement and numerical simulation. Validation of PR-DNS using PIV data. Abstract: In this work, a detailed comparison of velocity fields obtained from Particle Image Velocimetry (PIV) experimental measurement and Particle-Resolved Direct Numerical Simulation (PR-DNS) of flow inside a square duct around a train of five spherical particles at a Reynolds number of 100 based on the particle diameter Dp for two different particle separation distances of l/Dp ( l is the center to center distance between two neighboring particles) of 1.38 and 2.19 was performed. The PR-DNS numerical results were validated with PIV experimental data. It is argued that validations using point-wise flow measurement (such as drag on particle) are potentially unreliable for simulation verification and hence, field comparisons are needed. In addition, conclusions are drawn about the interaction of flow with spherical particles in the arrangement depending on the distance over diameter ratio and drag coefficient on the spheres were calculated.